St. Vincent and the Grenadines : Staff Report for the 2012 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2014)
KEY ISSUES Background: Activity is slowly recovering after a cumulative decline of about 5 percent during 2008-10. Expansionary fiscal policies-largely to counteract the impact of the global slowdown and the two successive natural disasters-led to a deterioration in fiscal balances, with public debt up by about 10 1\2 percent of GDP over this period. The fiscal deficit, however, is expected to narrow this year, largely reflecting cuts in capital spending. In the financial sector, non performing loans remain above prudential guidelines; provisioning and profitability are low; and supervision remains weak. Policy Challenges: Further fiscal consolidation-including by rebalancing government expenditure toward growth and employment generating public sector projects-is required to ensure medium-term sustained growth as well as keep public sector debt on a downward trajectory. In this regard, improving the efficiency of revenue collection and reducing current spending-especially on the wage bill, which is high relative to revenues-will be crucial to allow the government to maneuver fiscal policy. Financial sector weaknesses also need to be addressed, including through strengthening of supervisory and regulatory standards, to promote effective financial intermediation that supports private sector growth. Structural reforms, including infrastructure enhancements and labor market reforms are critical to improve competitiveness and ensure medium-term growth and current account sustainability.